"How to Improve Restaurant Productivity and Reduce Turnover with Qualified Workers in Uzbekistan" (Czech Journal of Multidisciplinary Innovations, 2023)
The restaurant industry pertains to the provision of catering services in various establishments such as restaurants, bars, and cafes. Uzbekistan is renowned for its delectable traditional cuisine, and it is imperative to promote its restaurants and support the growth of restaurateurs in the country. In terms of tax expectations, the government is actively implementing reforms to fully disclose Uzbekistan's economic and human potential by utilizing its competitive advantages. Sectors that can boost the country's economic development receive initial attention and support. With these insights, it is crucial to explore methods to enhance service quality and minimize employee turnover in Uzbekistan's restaurants and catering industry